Essence, structure and factors of economic sustainability of educational organizations in the conditions of a market environment - D. M. Shabanov (Новые технологии)
The article deals with the essence, structure and determinants of economic sustainability of educational organizations in a market economy. Literary sources have been analyzed and a conclusion has been made about the need to consider economic stability as a certain state of dynamic equilibrium in which the educational organization is located for effective functioning and development. In turn, economic sustainability is provided by the mechanism of self-organization (adaptation).